Graphical Methods Used to Solve Misalignment Problems of Mechanical Transmissions: Array - Stoica, Ramona-Monica; Voicu, Daniela; Vilău, Radu (Acta Universitatis Danubius. Œconomica, 2021)
This paper presents some graphical methods used to solve different misalignment problems of mechanical transmissions. For this purpose, it was created a mechanical transmission composed of an electric motor with a driving shaft, a coupling and a driven shaft mounted on two pillow block bearings. With the use of two dial indicators, there were measured both parallel and angular misalignment of the constituent elements and follow-up, it was realised a graphic display of the measured values, in order to determine the needed adjustments. Such alignment method has a high level of precision and it does not imply expensive devices. Misalignment of mechanical transmissions represents a broad issue in all factories, and the working personnel is constantly interested in ways to remedy such problems.